2007
DOI: 10.1002/hep.21885
|View full text |Cite
|
Sign up to set email alerts
|

Hemochromatosis genotypes and risk of 31 disease endpoints: Meta-analyses including 66,000 cases and 226,000 controls

Abstract: Hemochromatosis genotypes have been associated with liver disease, diabetes mellitus, heart disease, arthritis, porphyria cutanea tarda, stroke, neurodegenerative disorders, cancer, and venous disease. We performed meta-analyses including 202 studies with 66,263 cases and 226,515 controls to examine associations between hemochromatosis genotypes C282Y/C282Y, C282Y/H63D, C282Y/wild type, H63D/H63D, and H63D/wild type versus wild type/wild type and 9 overall endpoints and 22 endpoint subgroups. We also explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
97
6
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 28 publications
9
97
6
1
Order By: Relevance
“…Similarly, there was no significant difference between C282Y homozygotes and controls in the prevalence of most other self-reported symptoms commonly associated with hemochromatosis, including diabetes mellitus. The lack of association between HFE mutations and diabetes is consistent with the results of some (16,24,36,37), but not all (32,38) previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, there was no significant difference between C282Y homozygotes and controls in the prevalence of most other self-reported symptoms commonly associated with hemochromatosis, including diabetes mellitus. The lack of association between HFE mutations and diabetes is consistent with the results of some (16,24,36,37), but not all (32,38) previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study of first-degree relatives of patients with known C282Y hemochromatosis also found a low prevalence of clinical manifestations in family members who were C282Y homozygotes or C282Y/H63D compound heterozygotes, despite evidence of iron overload in most cases (31). However, a recent meta-analysis (32), based mainly on case-control studies, found an increased risk of liver disease among C282Y homozygotes compared to wild type/ wild type control subjects. In that study, hemochromatosis genotypes were not associated with an increased risk of diabetes mellitus, heart disease, arthritis, stroke or cancer in the overall analysis, although there was an increased risk of diabetes mellitus in C282Y homozygotes compared with controls among subjects of northern European descent.…”
Section: Discussionmentioning
confidence: 99%
“…A recent metaanalysis has shown that HFE genotypes encoding variants C282Y and/or H63D are associated with a 2-to 48-fold increased risk of PCT compared with the wild-type homozygote, with the C282Y/ C282Y conferring the highest risk (19 ). Increased frequencies of C282Y homozygotes, C282Y/H63D compound heterozygotes, and H63D homozygotes were seen in our PCT patients, compared with the general Norwegian population, but no association was seen for S65C.…”
Section: Discussioncontrasting
confidence: 40%
“…There is evidence that HFE C282Y/C282Y (4,5), as well as iron overload independent of HFE genotype (6), both confer a risk of diabetes. There is also evidence for increased risk of premature death due to organ damage in patients with clinically overt hereditary hemochromatosis (7)(8)(9)(10)(11) in individuals from the general population with increased transferrin saturation (TS) (12), independent of HFE genotype (13), and in patients with diabetes and increased TS or HFE genotype from a highly specialized diabetes clinic, the Steno Diabetes Centre (Gentofte, Denmark) (14).…”
mentioning
confidence: 99%